PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN KARTU SOAL UNTUK MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS SISWA PADA MATERI HIDROKARBON DI KELAS X-5 SMAN 4 BANJARMASIN - Rachmawaty Rachmawaty; Sunarti Sunarti (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2015)
Abstract: A research on the application of TGT-assisted learning model question cards to improve students learning outcomes and activities of the hydrocarbon material in class X-5 SMAN 4 Banjarmasin. This study aims to determine (1) the teacher in managing classroom activities, (2) students during the learning activity, (3) Results of student learning, and (4) Response X-5 grade students of SMAN 4 Banjarmasin the TGT-assisted learning model cards matter in hydrocarbon material. The method of research is a class act. The subjects were students of SMAN 4 Banjarmasin class X-5 as many as 36 people. Data collection techniquesusing objective tests, observation sheets and questionnaires. The results showed that the implementation of learning by using a card-assisted learning model TGT matter (1) Improving the quality of teacher activity at 55.28 at 60.25 first cycle to the second cycle with either category, (2) Improving the quality of student activityby 37 cycles I became 52.26 with either category, (3) Improving the quality of learning on cognitive learning outcomes in the first cycle of 61.11% to 88.89% in the second cycle, and the affective behavior characterized by an increase of 11.06 on the character quality 12.41 on the first cycle to the second cycle, the social skills of students in the first cycle of 14.74 has increased the quality of social be 14.36 in the second cycle with either category, (4) students gave a positive response.Keywords: TGT, question card, hydrocarbon